Karakteristik obyek hasil dari berbagai macam teknik filtering - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Basically, there are only three features in GIS (Geographic Information System), namely: node, arc, and polyline. A node is a unique representation of spatial information that is represented by an (X,19 or Ow) coordinate system. An arc is relation between two nodes or more, and a polyline is relation of some nodes where .the starting node is same as the ending node. In image processing, especially in pattern recognition, nodes, arcs, and polylines can be associated with and have the same characteristic as points, lines, and area. Filtering techniques have been widely used in image processing for image enhancement, reducing noise, or increasing quality of image, for example: low pass filtering median filtering, and high pass filtering. These techniques are used to be applied in an image with a raster data format. On the other hand, the most popular application of GIS was in vector data form. Although there is' a,method of conversion from raster format data to vector form or vice versa, but it loses some important information. This paper tries to evaluate the chdracteristic of an object that is extracted from image. The research shows the characteristic of the output image is the same with the characteristic of the filter that was applied, but the filter can not isolate the different objects, such as a point object from a line object.